Serum Exosomes MicroRNAs Are Novel Non-Invasive Biomarkers of Intrahepatic Cholestasis of Pregnancy - Dong, Ruirui; Ye, Ningzhen; Wang, Jing; Zhao, Shaojie; Wang, Tiejun; Wang, Gaoying; Shi, Xinrui; Cheng, Jing; Zhang, Yan; Yao, Tingting; Chen, Minjian; Zhang, Ting; et al. (Frontiers in Endocrinology, 2022)
Background Intrahepatic cholestasis of pregnancy (ICP) is closely related to the occurrence of adverse outcomes. Currently, total bile acids (TBAs) are the only diagnostic index for ICP, and its sensitivity and specificity have certain limitations. In this study, we aimed to develop potential biomarkers for the diagnosis of ICP. Methods Sixty pregnant women diagnosed with ICP and 48 healthy pregnant controls were enrolled in this study. We used the Agilent microRNA (miRNA) array followed by quantitative reverse transcriptase polymerase chain reaction assays to identify and validate the serum exosome miRNA profiles in ICP and healthy pregnant controls. We employed bioinformatics to identify metabolic processes associated with differentially expressed serum exosome miRNAs. Results The expression levels of hsa-miR-4271, hsa-miR-1275, and hsa-miR-6891-5p in maternal serum exosomes were significantly lower in ICP patients compared to controls; the diagnostic accuracy of hsa-miR-4271, hsa-miR-1275, and hsa-miR-6891-5p was evaluated with the area under the receiver operating characteristic curve (AUC) values of 0.861, 0.886, and 0.838, respectively. Multiple logistic regression analysis showed that a combination of the levels of hsa-miR-4271and hsa-miR-1275 afforded a significantly higher AUC (0.982). The non-error rate of a combination of all three exosome miRNAs was the highest (95%), thus more reliable ICP diagnosis. The expression levels of all three exosome miRNAs were negatively associated with TBAs. Furthermore, according to bioinformatics analysis, the three exosome miRNAs were related to lipid metabolism, apoptosis, oxidative stress, and the Mitogen Activated Protein Kinase (MAPK) signaling pathway. Conclusions This study may identify the novel non-invasive biomarkers for ICP and provided new insights into the important role of the exosome miRNA regulation in ICP.